Structured follow-up pathway to support people after transient ischaemic attack and minor stroke (SUPPORT TIA): protocol for a feasibility study and process evaluation - Grace M Turner; Melanie Calvert; Sue Jowett; Robbie Foy; Jonathan Mant; Sarah Tearne; Lou Atkins; Rachael Jones; Smitaa Patel; Phillip Collis (BMJ Open)
Introduction People who experience transient ischaemic attack (TIA) and minor stroke have limited follow-up despite rapid specialist review in hospital. This means they often have unmet needs and feel abandoned following discharge. Care needs after TIA/minor stroke include information provision (diagnosis and stroke risk), stroke prevention (medication and lifestyle change) and holistic care (residual problems and return to work or usual activities). This protocol describes a feasibility study and process evaluation of an intervention to support people after TIA/minor stroke. The study aims to assess the feasibility and acceptability of (1) the intervention and (2) the trial procedures for a future randomised controlled trial of this intervention.Methods and analysis This is a multicentre, randomised (1:1) feasibility study with a mixed-methods process evaluation. Sixty participants will be recruited from TIA clinics or stroke wards at three hospital sites (England). Intervention arm participants will be offered a nurse or allied health professional-led follow-up appointment 4 weeks after TIA/minor stroke. The multifaceted intervention includes: a needs checklist, action plan, resources to support management of needs, a general practitioner letter and training to deliver the intervention. Control arm participants will receive usual care. Follow-up will be self-completed questionnaires (12 weeks and 24 weeks) and a clinic appointment (24 weeks). Follow-up questionnaires will measure anxiety, depression, fatigue, health related quality of life, self-efficacy and medication adherence. The clinic appointment will collect body mass index, blood pressure, cholesterol and medication. Assessment of feasibility and acceptability will include quantitative process variables (such as recruitment and questionnaire response rates), structured observations of study processes, and interviews with a subsample of participants and clinical staff.Ethics and dissemination Favourable ethical opinion was gained from the Wales Research Ethics Committee (REC) 1 (23 February 2021, REC reference: 21/WA/0036). Study results will be published in peer-reviewed journals and presented at conferences. A lay summary and dissemination strategy will be codesigned with consumers. The lay summary and journal publication will be distributed on social media.Trial registration number ISRCTN39864003.